Metals speciation, separation, and recovery - International Symposium on Metals Speciation, Separation, and Recovery (2nd : 1989 : Rome, Italy); Patterson, James William, 1940-; Passino, Roberto; Industrial Waste Elimination Research Center (U.S.); Istituto di ricerca sulle acque (Italy) (Chelsea, MI : Lewis Publishers, 1990)
165118